Green synthesis of silver nanoparticles from Mahonia fortunei extracts and characterization of its inhibitory effect on Chinese cabbage soft rot pathogen - Wei, Zhenlin; Xu, Shuoqi; Jia, Haoran; Zhang, Hongmei (Frontiers in Microbiology, 2022)
The pathogenic bacterium Pectobacterium carotovorum causes soft rot in cabbage and significantly reduces plant yield. In this study, we employed Mhonia fortunei extracts to synthesis silver nanoparticles (Mf-AgNPs) and investigated their functions against P.carotovorum. The results showed that the surface plasmon resonance (SPR) peak of AgNP was 412 nm under optimal synthesis conditions. Furthermore, the results of Scanning electron microscope-Energy dispersive spectrometer (SEM-EDS) and High-resolution transmission electron microscopy (HR-TEM) revealed that the Mf-AgNPs had a spherical structure with an average diameter of 13.19 nm and the content of Ag0 ions accounted for 82.68% of the total elemental content. The X-Ray diffraction (XRD) results confirmed that AgNPs had a face-centered cubic (FCC) crystal structure, while Fourier transform infrared spectroscopy (FTIR) results indicated the presence of various biomolecules as reducing and stabilizing agents on the AgNP surface. Antibacterial activity was first evaluated by an inhibitory zone test, which revealed that 500 μg.mL-1 of AgNPs had antibacterial activity against P.carotovorum and four model bacteria including Staphylococcus aureus, Escherichia coli, Bacillus subtilis, and Pseudomonas aeruginosa, respectively with an antibacterial function comparable to 1 mM AgNO3 solution. The Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values for P.carotovorum were 8 μg.mL-1, respectively. Furthermore, AgNPs at 8 μg.mL-1 completely inhibited the growth of P.carotovorum, decreased their tolerance to 0.25 mM H2O2 as well as considerably reduced colony formation after 1 hour of treatment and thereafter. Treatment with Mf-AgNPs resulted in bacterial cell membrane destruction and biofilm formation inhibition, respectively. With an FIC (fractional inhibitory concentration) index of 0.174, AgNP and zhongshengmycin showed a significant synergistic effect. The infection of P.carotovorum to cabbage explants was significantly inhibited in vitro by a combination of 2 μg.mL-1 Mf-AgNP and 5 μg.mL-1 zhongshengmycin. In conclusion, the synthesized Mf-AgNP exhibited significant antibacterial activity against P.carotovorum.